2019
DOI: 10.1128/mbio.00469-19
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Proteomic Characterization of the Cyst Wall from In Vitro Toxoplasma gondii Cysts

Abstract: The tissue cyst of Toxoplasma gondii, found in latent infection, serves a critical role in both transmission and reactivation of this organism. Within infected cells, slowly replicating parasites (bradyzoites) are surrounded by a cyst matrix, cyst wall, and cyst membrane. The cyst wall is clearly delineated by ultrastructural analysis; however, the composition and function of this layer in host-parasite interactions are not fully understood. In order to understand the composition of the cyst wall, a proteomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 37 publications
9
113
0
1
Order By: Relevance
“…Consistent with previously reported data, we found that GRA12 is secreted into the PV, co‐localized with GRA2 detected using polyclonal rabbit anti‐GRA12 or anti‐HA antibody, and is associated with the IVN. GRA12 was also localized to the cyst wall and matrix, confirming previous proteomic finding that GRA12 exists in the cyst wall fractions …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previously reported data, we found that GRA12 is secreted into the PV, co‐localized with GRA2 detected using polyclonal rabbit anti‐GRA12 or anti‐HA antibody, and is associated with the IVN. GRA12 was also localized to the cyst wall and matrix, confirming previous proteomic finding that GRA12 exists in the cyst wall fractions …”
Section: Discussionsupporting
confidence: 88%
“…GRA12 was also localized to the cyst wall and matrix, confirming previous proteomic finding that GRA12 exists in the cyst wall fractions. 47 The IVN serves diverse functions, such as nutrient acquisition through trafficking of host-derived vesicles, 48 uptake | 3175 WANG et Al.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous tagging of two additional strong, early markers of differentiation (TGME49_312330, TGME49_208740) identified both as cyst-wall proteins, confirming the localization recently shown for TGME49_208740 ( Fig. S8C) (Tu et al, 2019). While BFD1 transcription is not exclusive to bradyzoites, BFD1 is identified as modestly upregulated at 72 h in stressed wild-type parasites by our scRNA-Seq data, and is significantly enriched in bradyzoite-containing clusters ( Fig.…”
Section: Characterizing Toxoplasma Cell-cycle Progression and Differesupporting
confidence: 88%
“…The log2 fold changes in protein abundance for MIC7 and the bradyzoite-specific marker, MAG1 ( (Tu et al, 2019); Figure 5A, Table S4) revealed that in contrast to MAG1, MIC7 is expressed in tachyzoites, supporting the MS and transcriptional evidence in ToxoDB. We next aimed to validate the protein's myristoylation as our MS screen did not identify a myristoylated peptide for MIC7.…”
Section: Mic7 Is Myristoylated and Is Important For T Gondii Lytic Csupporting
confidence: 54%